1983
DOI: 10.1016/0014-5793(83)80469-4
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of a heat‐stable enterotoxin isolated from enterotoxigenic Escherichia coli strain 18D

Abstract: A heat-stable enterotoxin produced by a strain of enterotoxigenic Escherichia coli 18D was purified by ionexchange and reversed-phase high-pressure liquid chromatography. The amino acid sequence of the purified toxin was determined by Edman-degradation and a combination of fast atom bombardment mass spectrometry and carboxypeptidase digestion to be Asn-Thr-Phe-Tyr-Cys-Cys-Glu-Leu-Cys-Cys-Asn-ProAla-Cys-Ala-Gly-Cys-Tyr.Enterotoxin Isolation Amino acid sequence FAB mass spectrometry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 13 publications
2
73
0
Order By: Relevance
“…Furthermore, the 1H-NMR spectra of these peptides were identical with that of standard STh (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), as shown in fig.5. Thus, we conclude that the disulfide linkages in STh (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) are formed between Cys-6 and Cys-11, Cys-7 and Cys-15, and Cys-10 and Cys-18, as shown in fig.6. We recently found that STp(5-17), which has Ala in place of Thr in STn (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), has the same disulfide bonds as STh(6--18) (not shown).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Furthermore, the 1H-NMR spectra of these peptides were identical with that of standard STh (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), as shown in fig.5. Thus, we conclude that the disulfide linkages in STh (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) are formed between Cys-6 and Cys-11, Cys-7 and Cys-15, and Cys-10 and Cys-18, as shown in fig.6. We recently found that STp(5-17), which has Ala in place of Thr in STn (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), has the same disulfide bonds as STh(6--18) (not shown).…”
Section: Resultsmentioning
confidence: 56%
“…Correspondence address: Y. Shimonishi, Institute for Protein Research, Osaka University, Suita, Osaka 565, Japan [7][8][9], as shown in fig. 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat-stable enterotoxin (STa) of Escherichia coli is an 18 or 19 amino acid peptide toxin (STp or STh) that causes diarrhea in humans and domestic animals [1,2]. STa binds to a cell surface receptor (STaR/GC-C) [3][4][5][6] in the intestine, which subsequently leads to activation of a guanylyl cyclase (GC) catalytic domain resulting in an accumulation of intracellular cyclic GMP (cGMP).…”
Section: Introductionmentioning
confidence: 99%
“…Two kinds of STa molecules which vary only slightly have been identified; an STa subtype (STaI) produced by ETEC isolated from both humans and pigs which is 18 amino acids long and another (STaII) only isolated from strains infecting humans which is 19 amino acids in length [4,5]. Both enterotoxins have six cysteines which are known to form intra-chain disulfide bridges [5].…”
Section: Introductionmentioning
confidence: 99%